PERLINDUNGAN NEGARA TERHADAP PRIVASI DATA PRIBADI DALAM LAYANAN SIM CARD DI ERA DIGITAL - Widigdo, Zefaki; Rosando, Abraham Ferry (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Personal data is fundamentally owned by everyone, often someone’s personal data is misused by some people for the purpose of making a profit by selling someone’s personal data. The sale of personal data is usually carried out on various sites and social media at different prices that have been set by the perpetrator. A person’s personal data obtained is identical to cybercrime, namely hackers. A hacker is someone who is an expert in the field of technology and information who is able to retrieve databases by breaking into cybersecurity. The potential that can occur if personal data becomes public consumption or is held by someone will entrust the owner of personal data such as used for online loans, used by online gambling sites and so on. The loss of the owner of the personal data can be felt both materially and immaterially. There are so many victims of personal data leaks who complain about concerns about becoming public consumption. Based on this, this research aims to protect everyone’s right to privacy to personal data. This research uses normative juridical research methods, with a statutory approach (Statute Aproache) and a conceptual approach to examine the legal protection of personal data from the consequences of sim card leaks, so that later a perscriptive conclusion is obtained. The right to protection of personal data has been guaranteed by law as stated in article 28G of the 1945 Constitution. The results of this study are expected to be able to provide views and solutions in addition to Indonesian law that has not been specifically regulated regarding the protection of personal data